Small antenna handbook - Hansen, Robert C. (John Wiley & Sons, 2011)
"This book addresses the recent significant theoretical and practical developments in the electrically small antenna area. It explains work on electromagnetically coupled structures, improving bandwidth using spherical helix dipoles, the exact derivation of the Q for electrically small antennas for both TE and TM modes, a new simplified Q formula developed by the authors, and provideds an expanded discussion of metamaterials and computer model accuracy for ESA"--